2007
DOI: 10.1038/sj.eye.6702973
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical trial of topical anaesthetic agents for cataract surgery with phacoemulsification: lidocaine 2% drops, levobupivacaine 0.75% drops, and ropivacaine 1% drops

Abstract: Purpose To assess the safety and efficacy of topical lidocaine, levobupivacaine, and ropivacaine in cataract surgery with phacoemulsification. Methods One hundred and five patients scheduled for cataract surgery with topical anaesthesia were randomly allocated into 3 groups of 35 patients each to receive eye drops of lidocaine 2%, levobupivacaine 0.75%, or ropivacaine 1% every 5 min starting 30 min before surgery. Patients graded their pain using a 0-10-point verbal pain score (VPS) at different stages of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…[1][2][3][4][5][6] Lidocaine, ropivacaine, and levobupivacaine are 3 commonly used topical anesthetic agents in modern cataract surgery. [7][8][9] Topical anesthesia does not provide adequate motor and sensory anesthesia and may be associated with increased intraoperative pain and complications. 4 Therefore, intracameral injection of unpreserved lidocaine 1% has become a commonly used adjunctive anesthetic agent during cataract surgery.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Lidocaine, ropivacaine, and levobupivacaine are 3 commonly used topical anesthetic agents in modern cataract surgery. [7][8][9] Topical anesthesia does not provide adequate motor and sensory anesthesia and may be associated with increased intraoperative pain and complications. 4 Therefore, intracameral injection of unpreserved lidocaine 1% has become a commonly used adjunctive anesthetic agent during cataract surgery.…”
mentioning
confidence: 99%
“…It provided sufficient and long-lasting analgesia without the need for supplemental intracameral anesthesia in most cases [10]. In a relative study, Borazan et al, concluded that topical anesthesia with ropivacaine was safe, feasible and more effective than lidocaine in cataract surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Before commencing our study, the only published data on topical ocular surface anesthesia with ropivacaine were cataract and pterygium extraction operations [9][10][11]. We wished to determine whether ropivacaine as the sole anesthetic could provide satisfactory ocular surface anesthesia for intraocular injection procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro and in vivo studies have confirmed the toxic effect of lidocaine on ganglion cells. [10,11] Furthermore, the short duration of the local anesthetic makes administration of a second dose during cataract surgery necessary, thus increasing the risk of toxicity. Ropivacaine, which has recently been introduced in clinical surgery, can represent a valid alternative to lidocaine in intracameral anesthesia.…”
Section: Short Communicationmentioning
confidence: 99%